Evaluation of Turkey’s Road-Based Greenhouse Gas Inventory and Future Projections - Şenay Çetin Doğruparmak; Kazım Onur Demirarslan; Samet Volkan Çavuşoğlu (Applied Sciences, 2025)
As road traffic in Turkey is a significant source of emissions due to the increasing number of vehicles on the road, the goal of this study is to calculate greenhouse gas emissions from Turkey’s roads between 2010 and 2020, create an inventory, and estimate possible emissions until 2050. In the study, both greenhouse gases (carbon dioxide (CO2) and nitrous oxide (N2O) and co-emitting air pollutants that indirectly contribute to climate change (ammonia—NH3, nitrogen oxide—NOX, sulfur dioxide—SO2, carbon monoxide—CO, non-methane volatile organic compounds—NMVOC, and particulate matter—PM) were investigated. The study revealed that the total number of vehicles using state roads in Turkey increased by 60% between 2010 and 2020. As a result, emissions of CO2, N2O, NH3, NOX, SO2, CO, NMVOC, and PM increased by 29.6%, 24.2%, 0.5%, 19.9%, 9.9%, 18.2%, 21.5%, and 39.7%, respectively. When emissions were analyzed on a provincial basis, particular attention was drawn to provinces with high levels of urbanization. Based on forecast studies, the total number of vehicles registered for traffic will increase by 105% by 2050. Due to this increase, CO2, N2O, NH3, NOX, SO2, CO, NMVOC, and PM emissions are estimated to increase by 149.17%, 151.78%, 154.39%, 138.95%, 150.97%, 153.09%, 152.09%, and 151.47%, respectively.